2021
DOI: 10.3390/cells10020438
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Monoclonal Gammopathies Linked to Poliovirus or Coxsackievirus vs. Other Infectious Pathogens

Abstract: Chronic stimulation by infectious pathogens or self-antigen glucosylsphingosine (GlcSph) can lead to monoclonal gammopathy of undetermined significance (MGUS) and multiple myeloma (MM). Novel assays such as the multiplex infectious antigen microarray (MIAA) and GlcSph assays, permit identification of targets for >60% purified monoclonal immunoglobulins (Igs). Searching for additional targets, we selected 28 purified monoclonal Igs whose antigen was not represented on the MIAA and GlcSph assays; their specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
(56 reference statements)
2
4
0
Order By: Relevance
“…In addition, high similarity was observed with VP1 N-termini of vaccine-derived polioviruses (VDPVs), namely VDPV3 (VDPV3/EST/Env2008 (GenBank: KC784372.1, Figure 3a). Of note, analysing our MVA data we found that seroreactivity to the recently described peptide sequences PALTAVETG and PALTAAETG, derived of the VP1 proteins of human PV-1/3 and CV-B1/B3 viruses and also shared by many other picornaviruses, 42 did not differentiate MI cases from controls (Figure S7), further confirming the functional relevance of the G-I-X-D findings. Then, we used conventional ELISA method to measure IgG response in Estonia I cohort sera (n = 14; same samples as in Figure 2a) against VP1 of several enteroviral species, including coxsackieviruses B1, B3 and B5 and with reported cross-reactivity to poliovirus type 3.…”
Section: Conservation Of the Antibody G-i-x-d Epitopes Across The Enteroviral Speciessupporting
confidence: 70%
“…In addition, high similarity was observed with VP1 N-termini of vaccine-derived polioviruses (VDPVs), namely VDPV3 (VDPV3/EST/Env2008 (GenBank: KC784372.1, Figure 3a). Of note, analysing our MVA data we found that seroreactivity to the recently described peptide sequences PALTAVETG and PALTAAETG, derived of the VP1 proteins of human PV-1/3 and CV-B1/B3 viruses and also shared by many other picornaviruses, 42 did not differentiate MI cases from controls (Figure S7), further confirming the functional relevance of the G-I-X-D findings. Then, we used conventional ELISA method to measure IgG response in Estonia I cohort sera (n = 14; same samples as in Figure 2a) against VP1 of several enteroviral species, including coxsackieviruses B1, B3 and B5 and with reported cross-reactivity to poliovirus type 3.…”
Section: Conservation Of the Antibody G-i-x-d Epitopes Across The Enteroviral Speciessupporting
confidence: 70%
“…Previous reports have suggested an association between MGUS, MM and infection. In particular, we and others showed that at least one-third of MGUS and MM cases present with a monoclonal Ig that targets an infectious pathogen, including HCV ( 17 , 22 , 23 , 26 28 ). The recent in vivo demonstration that chronic antigen stimulation can lead to emergence of clonal plasma cells supports the role of chronic infection in the development of subsets of MGUS and MM ( 15 ).…”
Section: Discussionmentioning
confidence: 92%
“…Presently, the infection which drives MGUS or MM can be identified in 60% MGUS patients and 33% of MM patients ( 9 , 10 ). As disease progression has been associated with dysbiosis in mice ( 14 ), Jasiński et al.…”
Section: Role Of the Microbiotamentioning
confidence: 99%
“…Although MGUS is most often asymptomatic, patients may present with renal, neurological or skin symptoms of various severity (for instance, monoclonal gammopathies of renal significance (MGRS)) (6)(7)(8). Associations between MGUS and autoimmune disorders, infection and recently, gut microbiota, are established (3,5,9,10,(14)(15)(16)(17)(18)(19)(20)(21)(22). Importantly, several groups demonstrated that monoclonal Ig from MGUS and MM patients specifically target either a self-antigen (including myelin-associated glycoprotein (MAG), glucosylsphingosine (GlcSph, in 13-15% MGUS/MM cases), other gangliosides, different membrane components) or an antigen from an infectious pathogen (including HCV, HBV, HIV, EBV, other Herpesviruses, Helicobacter pylori, or Enteroviruses, in 60% MGUS and 33% MM).…”
mentioning
confidence: 99%
See 1 more Smart Citation